A MODIFIED METHOD FOR DETERMINATION OF SCALE FACTOR OF THE PROJECTED GEODESIC (Journal of Engineering, 2006)
Conformal projection is one of the most important aspects that geodesy dealing with. Thedetermination of the scale factors in the meridian, the parallel and projected geodesic directions are thefinal result of the conformal projection. Methods for determining the scale factors in the meridian andthe parallel directions have a quite sufficient accuracy. While methods for determining the projectedgeodesic have different accuracy and computation complicity.This research adopts a modified method for computing the exact value of scale factor ingeodesic direction. In this method the scale factor is obtained by determining the true and projecteddistances of the geodetic line. In the traditional methods for determining the projected distance it isusual to use the 1/3 Simpson's rule in the computations while the modified method the 3/8 Simpson'srule is used.Computations and mathematical tests were carried out to obtain the scale factors using thetraditional methods and comparison was made with modified method.By applying the developed method and the traditional methods to calculate the scale factor, it wasfound that the modified method is more accurate and the projected distances can be obtained exactly.